LakeCC: a tool for efficiently identifying lake basins with application to palaeogeographic reconstructions of North America - Hinck, Sebastian; Gowan, Evan J.; Lohmann, Gerrit (Journal of Quaternary Science, 2019)
Along the margins of continental ice sheets, lakes formed in isostatically depressed basins during glacial retreat. Their shorelines and extent are sensitive to the ice margin and the glacial history of the region. Proglacial lakes, in turn, also impact the glacial isostatic adjustment due to loading, and ice dynamics by posing a marine‐like boundary condition at the ice margin. In this study we present a tool that efficiently identifies lake basins and the corresponding maximum water level for a given ice sheet and topography reconstruction. This algorithm, called the LakeCC model, iteratively checks the whole map for a set of increasing water levels and fills isolated basins until they overflow into the ocean. We apply it to the present‐day Great Lakes and the results show good agreement (∼1−4%) with measured lake volume and depth. We then apply it to two topography reconstructions of North America between the Last Glacial Maximum and the present. The model successfully reconstructs glacial lakes such as Lake Agassiz, Lake McConnell and the predecessors of the Great Lakes. LakeCC can be used to judge the quality of ice sheet reconstructions.